Effectiveness of Schema Therapy on Ambiguity Tolerance, Social Competence, Family Emotional Atmosphere, and Individual Self-Efficacy Among Spouses of Individuals Seeking Treatment at Addiction Treatment Centers - Mohammadi, Fatemeh; Khayatan, Floor (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study examines the effectiveness of schema therapy on ambiguity tolerance, social competence, family emotional atmosphere, and individual self-efficacy among spouses of individuals seeking treatment for addiction. Methods and Materials: The research design is a quasi-experimental, pretest-posttest-follow-up format with control and experimental groups. The study population comprises spouses of individuals receiving addiction treatment in 2024. A sample of 30 participants was selected via convenience sampling and allocated to experimental (n=15) and control (n=15) groups using a simple random assignment technique. Data collection instruments included the Tolerance for Ambiguity Scale (McLain, 2009), the Social Competence Scale (Parandin, 2006), the Family Emotional Atmosphere Questionnaire (Hillburn, 1964), and the Individual Self-Efficacy Scale (Sherer, 1982). Findings: The intervention group received schema therapy over ten 90-minute sessions. Data were analyzed using repeated-measures ANOVA. Results indicate that schema therapy significantly enhances ambiguity tolerance, social competence, family emotional atmosphere, and individual self-efficacy among spouses of individuals in addiction treatment (p < 0.05). Conclusion: These findings suggest that schema therapy has a positive impact on improving these psychological and social outcomes.